To seduce a sinner [large type] - Hoyt, Elizabeth, 1970- (Hoyt, Elizabeth, 1970- Legend of the four soldiers series, 2009)
Melisande Fleming finally gets a chance to prove her love for rakish Lord Vale when he is jilted on his wedding day and she offers to marry him, but his nightmares and a deadly betrayal from the past threaten to tear them apart.